Effect of biofilms grown at various chloramine residuals on chloramine decay - Adhikari, Rekha; Sathasivan, Arumugam; Bal Krishna, K (IWA Publishing, 2012)
Maintaining longer lasting disinfectant residual in a distribution system is highly important to prevent microbial re-growth and hence to deliver safe drinking water. However, various factors such as microbes present in bulk water, sediment, or attached to pipe wall and biofilms accelerates the chloramine decay. Among them, biofilms are a major factor in accelerating chloramine decay as they provide a habitat for the microbes. Thus, this study investigates the effect of biofilms in terms of chloramine decay in the distribution system. Biofilms were grown under various chloramine residuals and different ages of biofilms were investigated by subjecting them to batch tests. Experimental results repeatedly showed that chloramine decay due to biofilms is independent of its growth condition, particularly for different chloramine residuals.